Effect of provenance and spacing on stem straightness and number of stems with spike knots in Pinus sylvestris L. - northern Sweden and countrywide models - Ståhl, Erik G.; Persson, Bengt; Prescher, Finnvid (1990)
Nine Scots pine (Pinus sylvestris L.) trials, situated north of latitude 6I0N, were studied. The frequency of trees with straight stems and one or more spike knots was evaluated at a tree age of 27-29 years. A model was developed describing geographical variation and was based on 19 provenance trials from different parts of Sweden. North of latitude 6I0N, an average of 30 per cent of the stems were straight enough to produce a first-class bottom log of sawtimber. In addition, 47 per cent of the trees had no spike knots up to 5 m height. Significant variation between provenances was found in stem straightness and spike knot frequency in most trials. Provenances transferred southwards were straighter and had fewer spike knots than the corresponding local provenance. The frequencies and numbers of straight stems and trees without spike knots were higher at 1.25 m spacing than at 2.0 m spacing. The general models for geographical variation indicate that the highest number of straight stems without spike knots may be found between latitudes 58" and 65"N and at altitudes below 250 m.